Coalescence law of microdroplet swarms in microchannels. (23rd November 2022) - Gao, Chenghao; Ling, Sida; Chen, Zhuo; Wang, Yundong; Xu, Jianhong
Highlights: The coalescence law of microdroplet swarms in microchannels was studied. The effects of operation conditions and physical parameters on droplet coalescence behavior were investigated. The mechanism of droplet coalescence was explained by liquid film drainage theory. Abstract: Droplet microfluidic technology refers to the technique of preparing and controlling microscale monodisperse droplets by shear force and interfacial tension of two immiscible phases accurately, which has a wide range of applications in biomedicine, chemical reaction enhancement, nanoparticle preparation, and other fields due to its efficient mass and heat transfer, easy manipulation, rapid response, and high throughput. In the application of droplet microfluidic technology, coalescence often occurs due to the structural complexity of microchannels, which limits the practical application performance. The mechanism of droplet coalescence has been widely studied in conventional reactors, among which the liquid film drainage theory is the most widely accepted. To achieve accurate control of the droplet coalescence process, there have been many studies on droplet coalescence in microchannels. A variety of microchannel structures have been proposed and the mechanism and influencing factors of double droplets coalescence have been explored. However, most of the existing studies on coalescence are based on cross structures, mainly studying the coalescence of double droplets in confined systems. There is still a lack of research on the coalescence process of droplet swarms, which is more widespread in practical applications. Therefore, this work used the rectangular expansion structure to realize the droplet coalescence and explored the effects of two-phase flow rate, continuous phase viscosity, surfactant concentration, and the size of expanding channel on the droplet coalescence behavior. The coalescence types, probabilities, and size distributions of microdroplet swarms under different factors were summarized. The time distribution of liquid film drainage in the droplet coalescence process and the influence of various factors on it were further analyzed based on the liquid film drainage theory.